Ozone photolysis: strong isotopologue/isotopomer selectivity in the stratosphere - Ndengué, Steve; Madronich, Sasha; Gatti, Fabien; Meyer, Hans-Dieter; Motapon, Ousmanou; Jost, Rémy (Journal of geophysical research. Atmospheres, 2014)
We calculated the photolysis rate coefficients of five ozone isotopologues/isotopomers as functions of altitude up to 80 km using recent ab initio absorption cross sections and an averaged actinic flux. Three of the five ozone isotopologues/isotopomers are symmetric, with a single isotopic dissociation channel, and two are asymmetric with two isotopic dissociation channels.
Gesehen am 29.07.2020